2022
DOI: 10.14341/dm12847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic HCV infection in patients with type 2 diabetes mellitus in Russia

Abstract: BACKGROUND: The poor outcomes of chronic hepatitis C (CHC) and type 2 diabetes determine the socio-economic significance of the combined pathology since they lead to premature death. The proportion of patients with type 2 diabetes with markers of viral hepatitis (VH) in the Russian Federation is not known, which does not allow us to estimate the burden for the state of this medical problem.OBJECTIVE: Assessment of the prevalence of concomitant pathology, HCV infection and type 2 diabetes, as well as the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…This finding was in accordance with these studies. 11 , 12 Another study done in Saudi Arabia also documented similar results. 13 …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This finding was in accordance with these studies. 11 , 12 Another study done in Saudi Arabia also documented similar results. 13 …”
Section: Discussionsupporting
confidence: 59%
“…This finding was in accordance with these studies. 11,12 Another study done in Saudi Arabia also documented similar results. 13 Furthermore, a cross-sectional observational study among T2DM patients in India found a significantly increased risk of hypothyroidism in the elderly > 65 years.…”
Section: Discussionmentioning
confidence: 60%
“…Abnormalities were significantly more common in females than in males and in insulin‐treated patients compared with patients on oral hypoglycaemic drugs. Subclinical hypothyroidism was most common (48.3%) followed by subclinical hyperthyroidism (23.1%) and clinical hypothyroidism (4.4%) 14 …”
Section: Discussionmentioning
confidence: 99%
“…Increased hexose absorption from the intestine in thyroxicosis 2 Reduced responsiveness to insulin in thyrotoxicosis 2,14 Increased release of catecholamines resulting from stress, which in turn causes (a) impaired insulin action on target tissue and increased hepatic glucose production, and (b) impaired disposal of exogenous glucose 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation